Analytical approaches for assessing business perspectives in the automotive industry of Ukraine - Poyda-Nosyk Nina; Pojda-Noszik Nina; Пойда-Носик Ніна; Robert Bacho; Bacsó Róbert; Бачо Роберт (Czestochowa University of Technology, 2023)
Abstract. The study examines the state and development trends of the automotive industry of Ukraine for the period 2016-2021. The trends of the labor market in Ukraine have been identified, the state of migration processes, the level of unemployment in the regions of Ukraine have been assessed. The results of a comparative analysis of the level of the minimum wage in Ukraine in terms of regions, categories and positions are presented. The standard salary of back-office workers and management in the automotive sector was studied. The evolution of the regulatory and legal provision of state regulation of the development of the automobile industry in Ukraine is traced. Radical changes in the state policy of the development of the automotive industry of Ukraine were revealed: from constant support of car manufacturers and stimulation of car production to bureaucratic barriers, obstacles and existing risks and threats. It is stated that since 2014, Russia's armed aggression against Ukraine has led to a significant decline in the car industry. Proximity to the border with the EU, cheap labor and sufficient raw materials make the western oblasts of Ukraine especially attractive for partnership with European auto giants.
https://wydawnictwo.pcz.pl/fcp/iGBUKOQtTKlQhbx08SlkTUQNHUWRuHQwFDBoIVURNFDgPW1ZpCFghUHcKVigEQR1BXQEsKTwdAQsKJBVYC RlYdxdFDy4Z/275/public/12th_international_conference_on_management_sustainability-security-quality_icom_2023_2.pdf
Keywords: automotive industry; development trends; dynamics of car manufacturing; the state support policy; labor market